Furan-Indole-Chromenone-Based Organic Photocatalyst for α-Arylation of Enol Acetate and Free Radical Polymerization Under LED Irradiation - Aurélien Galibert-Guijarro; Adel Noon; Joumana Toufaily; Tayssir Hamieh; Eric Besson; Stéphane Gastaldi; Jacques Lalevée; Laurence Feray (Molecules)
In this study we report on the efficiency of a furane-indole-chromenone-based organic derivative (FIC) as a photocatalyst in the α-arylation of enol acetate upon LED irradiation at 405 nm, and as a photoinitiator/photocatalyst in the free radical polymerization of an acrylate group in the presence of bis-(4-tert-butylphenyl)iodonium hexafluorophosphate (Iod) as an additive, or in the presence of both Iod and ethyl-4-(dimethyl amino) benzoate (EDB) under LED irradiation at 365 nm. The photochemical properties of this new light-sensitive compound are described, and the wide redox window (3.27 eV) and the high excited-state potentials FIC*/FIC●− (+2.64 V vs. SCE) and FIC●+/FIC* (−2.41 V vs. SCE) offered by this photocatalyst are revealed. The chemical mechanisms that govern the radical chemistry are discussed by means of different techniques, including fluorescence-quenching experiments, UV-visible absorption and fluorescence spectroscopy, and cyclic voltammetry analysis.